Teogogy Nationalistic: An Interaction Model of Christian Religious Education in a Multicultural Society in the Digital Era - Dirk Roy Kolibu (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research proposes the concept of nationalistic theogogy in the model of Christian religious education interaction in a multicultural society. This approach involves multicultural theology and pedagogy that complement each other in appreciating the cultural, ethnic, and religious diversity in a multicultural society. The concept incorporates fragments from experts exploring the relationship between religion, national identity, and education, particularly Christian religious education. The interaction model combines aspects such as intellectual virtues, morality rooted in faith, Bible-based humanism, inclusivity, human limitations, and teaching based on reliance on God. The model is expected to contribute to building a peaceful national insight and preserving diversity in a nationalistic context. The importance of interpersonal communication skills is also emphasized in this model, with the development of communication skills being a crucial aspect of social interaction. The model reflects the significance of effective communication in human life. In the digital era, Christian educational interactions in multicultural societies need to consider disruptions and utilize social media to develop inclusive and responsive interaction models that accommodate cultural and religious diversity. This research employs a qualitative method with a descriptive approach, involving the collection and inductive analysis of data to describe and understand the phenomena of Christian educational interactions in multicultural societies and the need to develop inclusive and responsive interaction models that accommodate cultural and religious diversity. By leveraging social media, Christian education can be more effective in achieving inclusion goals and responding to diversity in a multicultural society.